Registries on peritoneal surface malignancies throughout the world, their use and their options. (4th July 2017) - Verwaal, Victor J.; Rau, Beate; Jamali, Faek; Gilly, François Noël; de Hingh, Ignace; Takala, Heikki; Syk, Ingvar; Pelz, Jorg; Mulsow, Jurgen; van der Speeten, Kurt; Shigeki, Kusamura; Iversen, Lene H.; et al.
Abstract: Aim: The treatment of peritoneal surface malignancies ranges from palliative care to full cytoreductive surgery (CRS) and heated intraperitoneal chemotherapy, HIPEC. Ongoing monitoring of patient recruitment and volume is usually carried out through dedicated registries. With multiple registries available worldwide, we sought to investigate the nature, extent and value of existing worldwide CRS and HIPEC registries. Methods: A questionnaire was sent out to all known major treatment centres. The questionnaire covers: general purpose of the registry; inclusion criteria in the registry; the date the registry was first established; volume of patients in the registry and description of the data fields in the registries. Finally, the population size of the catchment area of the registry was collected. Results: Twenty-seven questionnaires where returned. National databases are established in northwest European countries. There are five international general databases. Most database collect data on patients who have undergone an attempt to CRS and HIPEC. Two registries collect data on all patients with peritoneal carcinomatosis regardless the treatment. Most registries are primarily used for tracking outcomes and complications. When correlating the number of cases of CRS and HIPEC that are performed to the catchment area of the various registry, a large variation in the number of performed procedures related to the overall population was noted, ranging from 1.3 to 57 patients/million year with an average of 15 patients/1 million year. Conclusions: CRS and HIPEC is a well-established treatment for peritoneal surface malignancies worldwide. However, the coverage as well as the registration of treatment procedures differs widely. The most striking difference is the proportion of HIPEC procedures per capita which ranges from 1.3 to 57 patients per million. This suggests either a difference in patient selection, lack of access to HIPEC centres or lack of appropriate data collection.